Survival of the fittest Small and Medium Enterprises: Accessing commercial bank funding in South Africa - Marimo, Mercy (Graduate School of Business (GSB), 2021)
Small and Medium Enterprises (SMEs) are touted as engines of sustainable economic growth. They span a wide spectrum of economic domains and are inclined to foster innovative entrepreneurship and gratify a variety of socio-economic objectives such as poverty alleviation, income generation, employment creation and reduction in societal inequalities. The SME sector in South Africa is challenged by slow growth in young businesses and dying at infancy due to lack of financial support. Inadequate funding results from a myriad of factors which include comprehensive enforcement of regulatory requirements, information asymmetry, moral hazards, lack of sound information on credit performance and technological divide. This study investigated this funding conundrum by assessing the success rate of SME applications for commercial funding. A quantitative cohort analysis was used on overdraft facilities obtained from one of the leading financial institutions in South Africa to determine the drivers of default. A time series view of macroeconomic factors and macroprudential indicators in conjunction with the demand and supply trends was analysed using vector autoregression techniques to determine the impact of the economic environment and financial market condition on access to funding. Unit root tests and cointegration analyses were applied to examine stationarity, shortrun and long-run relationships. The SME scorecard was developed using logistic regression on cohorts of applications over a seven-year observation period to determine the drivers of default as part of credit risk management. SME application scorecards were developed including and excluding bureau information. The ensuing models' ability to differentiate risk were assessed using Receiver Operating Characteristic (ROC) curves. The results show that, the demand and supply of SME credit is influenced by trends in the domestic, economic and financial environment. The robustness, stability and relevance of an application scorecard is enhanced by reject inference and the inclusion of bureau information. Small businesses operating in the service sector and having a long-standing rapport with the bank can easily access commercial bank funding. SMEs in the construction industry with a high number of credit enquiries are unlikely to survive the stringent conditions of the bank lending criteria. It is the prerogative of the principal business owner to honour their financial obligations across the credit industry if commercial bank funding is desired. Their credit quality forms the fulcrum of the lender's SME application scorecard.